2009
DOI: 10.1073/pnas.0909611107
|View full text |Cite
|
Sign up to set email alerts
|

DNA aptamer–micelle as an efficient detection/delivery vehicle toward cancer cells

Abstract: We report the design of a self-assembled aptamer-micelle nanostructure that achieves selective and strong binding of otherwise low-affinity aptamers at physiological conditions. Specific recognition ability is directly built into the nanostructures. The attachment of a lipid tail onto the end of nucleic acid aptamers provides these unique nanostructures with an internalization pathway. Other merits include: extremely low off rate once bound with target cells, rapid recognition ability with enhanced sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
200
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(203 citation statements)
references
References 19 publications
0
200
0
3
Order By: Relevance
“…One of its major sectors is nanoparticle drug delivery [1,3,6]. Nanotechnology-based drug delivery systems have emerged as promising platforms for targeting and destroying mainly cancer cells [7][8][9] via photodynamic therapy (PDT) that uses a combination of light sources, photosensitizers such as phthalocyanines, and specific targeting molecules and nano-carriers for localized therapies at the micro/nanoscale. Following light activation of photosensitizers, reactive oxygen species are released and eventually destroy cancer cells [10], after successful intracellular internalization via endocytosis and subsequent accumulation in the endosome/lysosome compartments of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…One of its major sectors is nanoparticle drug delivery [1,3,6]. Nanotechnology-based drug delivery systems have emerged as promising platforms for targeting and destroying mainly cancer cells [7][8][9] via photodynamic therapy (PDT) that uses a combination of light sources, photosensitizers such as phthalocyanines, and specific targeting molecules and nano-carriers for localized therapies at the micro/nanoscale. Following light activation of photosensitizers, reactive oxygen species are released and eventually destroy cancer cells [10], after successful intracellular internalization via endocytosis and subsequent accumulation in the endosome/lysosome compartments of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Various signal reporters have been adopted, including radioactive, magnetic, and fluorescent agents (9)(10)(11)(12)(13). Our group has demonstrated that near-infrared dye-labeled aptamers could effectively recognize cancer cells in vivo and achieve cancer imaging with high specificity (13).…”
mentioning
confidence: 99%
“…Similarly to the DBC micelle system, aptamers recognizing Ramos cells were assembled into micelles through implementation of a hydrophobic moiety at one end of the ODN. Interestingly, due to the multimerization of the aptamer sequence an increased binding of the micelles compared to the pristine nucleic acid sequence was achieved [159].…”
Section: Amphiphilic Dna Block Copolymersmentioning
confidence: 99%